Teaching Materials Needs: Student Worksheets in Exposition Text Learning - Sagitari, Wulanti; Purnomo, Mulyadi Eko; Ernalida, Ernalida (Journal of Education Reseach and Evaluation, 2021)
Indonesian language teachers in schools lack teaching materials. Even teachers don't have HOTS-oriented open materials. It will impact students who have difficulty in learning because they do not have learning resources. Professional educators must be able to develop teaching materials to address the learning objectives of the 2013 Curriculum in any learning situation. The readiness of teachers to carry out the teaching and learning process can be assisted by applying teaching materials that are by the 2013 curriculum. This study aims to conduct a needs analysis survey from various research and development stages to develop and validate products and determine appropriate teaching materials. The stages of research and development are applied from the learning process, analysis of targeted learning outcomes, and analysis of students and their needs. The research subjects consisted of class X students with a population of 185 students and 2 Indonesian language teachers. The number of samples is 28 students, or 15% of the population. The first data collection technique is a questionnaire of student needs and interviews. Based on the findings and discussion, the LKS recommended by researchers is the exposition LKS with a scientific plus approach. Students can practice it and find accurate information for the exposition text with this worksheet. On the other hand, teachers can also unite and facilitate students to construct their knowledge of the text.